Effectiveness of a culturally tailored text messaging program for promoting cervical cancer screening in accra, Ghana: a quasi-experimental trial - Adolphina Addoley Addo-Lartey; Harriet Affran Bonful; Ransford Selasi Sefenu; Timothy Agandah Abagre; Alexander Asamoah; Delia Akosua Bandoh; Adolf Kofi Awua; Nii Armah Adu-Aryee; Florence Dedey; Richard Mawuena Kofi Adanu; Kolawole Stephen Okuyemi (BMC, 2024)
Abstract Introduction Despite breakthroughs in cervical cancer detection, resource-constrained countries continue to have a disproportionately high incidence and death rate. Mhealth has been identified as an important tool for increasing cervical cancer screening rates in Sub-Saharan Africa. We determined whether sending Ghanaian women culturally tailored one-way mobile phone SMS text messages about cervical cancer would encourage the uptake of the human papillomavirus (HPV) test. Methods From August to November 2016, 88 women aged 18 to 39 living or working in an urban community (Accra, Ghana) participated in a quasi-experimental study. For 8 weeks, 32 SMS messages regarding cervical cancer were developed and sent to the personal phones of intervention arm participants (n = 42). Women in the control group (n = 46) received SMS texts with general health and lifestyle advice. Fischer's exact tests were performed to assess cervical cancer screening uptake and associated reasons for non-uptake between the intervention and control groups (p < 0.05). Results At the baseline, women differed in terms of ethnicity and wealth. After the intervention, participants' self-reported risk factors for cervical cancer, such as early menarche, usual source of medical treatment, family history of cancer, smoking, and alcohol history, changed. None of the women in the intervention group sought cervical cancer screening after the intervention, but only one (2.2%) of the control arm participants did. Almost all the women (> 95%) agreed that an HPV test was essential and that regular healthcare check-ups could help prevent cervical cancer. Some women believed that avoiding particular foods could help prevent cervical cancer (23.8% intervention vs. 58.7% control, p < 0.001). Time constraints and out-of-pocket expenses were significant barriers to cervical cancer screening. Conclusion: A one-way SMS delivered to urban women did not increase cervical cancer screening attendance. The time spent in screening facilities and the lack of coverage by the National Health Insurance Scheme limited screening uptake. We urge for the establishment of screening centers in all healthcare facilities, as well as the inclusion of cervical cancer screening in healthcare programs through cost-sharing.